Model Predict, Observe, Explain Berbantuan Time Sequence Card: Strategi Meningkatkan Keaktifan Belajar di MA Darul Huffaz - Ayu Anggraini; Umi Hijriyah; Ida Faridatul Hasanah (WISE Pendidikan Indonesia, 2026)
Student learning activity in Islamic Cultural History learning remains a challenge when instruction is dominated by conventional teacher-centered methods. Such learning conditions may limit students’ participation in asking questions, engaging in group discussions, observing historical events, and explaining historical materials coherently. This study aimed to examine the effect of the Predict, Observe,Explain (POE) learning model assisted by Time Sequence Card media on students’ learning activity in Islamic Cultural History at MA Darul Huffaz Pesawaran. This study employed a quantitative approach using a quasi-experimental method with a Posttest-Only Control Group Design. The sample consisted of 60 eleventh-grade students, comprising 30 students in the experimental class who received POE learning assisted by Time Sequence Cards and 30 students in the control class who received conventional instruction. Data were collected using a learning activity questionnaire covering students’ willingness to ask questions, participation in group discussions, and involvement in completing learning tasks. The data were analyzed using normality and homogeneity tests, followed by an independent-samples t-test using SPSS. The results showed a significance value of 0.005, which was lower than 0.05, indicating a statistically significant difference between the experimental and control groups. Therefore, the Predict, Observe, Explain learning model assisted by Time Sequence Card media had a significant effect on students’ learning activity in Islamic Cultural History learning.